A taxonomic synopsis of the Eccritotarsini (Hemiptera: Heteroptera: Miridae: Bryocorinae) of Colombia - Alvarez-Zapata, Alejandra; Ferreira, Paulo S. F.; Serna, Francisco (Zootaxa, 2022)
Eccritotarsini (Hemiptera: Heteroptera: Miridae: Bryocorinae) is a group of predominantly phytophagous true bugs, with 650 known species described in 112 genera worldwide. It is the most specious tribe within the subfamily, which is distributed primarily in the Neotropics. Previous studies of Eccritotarsini in Colombia recorded 13 genera and 30 species. In this work, utilizing material from five Colombian and two Brazilian insect collections, we examined 700 specimens representing species of the tribe from Colombia. Our study confirmed all previous records of genera and 20 out of 30 previous species for the country and include new records of 10 genera and 8 species. Moreover, we provide taxonomic keys, relevant diagnoses, and illustrations for adults. Additionally, we offer names of both related and host plant species, and the geographic distribution for each species.